Embracing peer review of teaching: promoting the ‘why’ within third space education. - Avril Buchanan; Kate Haley; Chad McDonald (Journal of Learning Development in Higher Education)
This case study explores how a Learning Development team has moved from a peer-observation to a peer-review process over the last five years, examining the rationale, development, and impact of the change in approach. The move to a peer-review process has emphasised a focus on holistic activity, through the connection of individual and group reflection on practice. We argue that the implementation of a peer-review process offers a way to recognise and ‘frame’ the complexity of career development for third-space educators (Veles and Carter, 2016). This is achieved by providing space in the process for individuals to develop their expertise, participate in peer discussions, share findings, and contribute to the shape of the team’s strategy. Importantly, the adopted peer-review process promotes ‘collegial conversations’ (Quinlan and Åkerlind, 2000, p.101) that are built on trust (O’Keeffe et al., 2021), rather than snap judgements about teaching. Consequently, we suggest that our peer-review process is an enabler for us as third-space educators to articulate the impact of our practice through both theoretical and practical lenses, helping us to influence positive change within contemporary higher education.